Context-Dependent Categorical Perception of Surprise. (March 2013) - Cheal, Jenna L; Rutherford, M D
Evidence regarding the categorical perception of surprise facial expressions has been equivocal. Surprise is inherently ambiguous with respect to valence: it could be positive or negative. If this ambiguity interferes with categorical perception, disambiguating the valence might facilitate categorical perception. Participants identified and discriminated images that were selected from expression continua: happy – fear, surprise – fear, happy – surprise. Half were presented with a context for the surprise expressions indicating positive or negative valence. Both groups had a typical identification curve, but discrimination performance was better predicted by identification in the context condition for happy – fear and surprise – fear continua, suggesting that categorical perception was facilitated by the disambiguating context.